The optimisation of microalgae growth in medium based on palm oil mill effluent (POME) from effluent of biogas plant of Felda Sg. Tengi palm oil mill / Jailani Salihon and Meor Ahmad Faez Mohd Hassan - Salihon, Jailani; Mohd Hassan, Meor Ahmad Faez (Universiti Teknologi MARA Shah Alam, 2018)
This paper reports on the effects of carbon dioxide (CO2) concentration and agitation rate on microalgae growth in medium based on the effluent of the biogas plant of Felda Sg. Tengi Palm Oil Mill supplemented with palm oil mill effluent (POME) from their first facultative pond. Two variables which are CO2 concentration (X1) and agitation rate (X2) are used to optimise the microalgae growth using a 22 factorial design which was complemented to make a composite design. The linear regression model was used to analyse the results of the 22 factorial experiment and determine whether it contains the maximum point. The quadratic regression model was used to analyse the results of the composite design experiments and optimise the microalgae growth based on maximum biomass concentration (xm). The theoretical maximum point for xm from the quadratic regression model was predicted to be at 16.03% CO2 concentration and 0.9 vvm agitation with the theoretical maximum xm predicted to be 42.6158 g/l.